The Role of Proactivity, Innovation and Digitalization in Driving Business Performance and Growth in Indonesia’s Shibori Tie-Dye Craft Industry - Arif Rakhmanto; Zunan Setiawan (IECON: International Economics and Business Conference, 2024)
This study aims to explore the role of digital technology in shibori fabric entrepreneurship. Specifically, the main objective of this research is to examine the relationship between proactivity, innovation, digitalization, and the performance and growth of businesses within the fabric craft industry. Data for this research were collected from 285 shibori fabric artisans residing in major cities on the island of Java at the time the study was conducted. The study uses PLS-SEM to analyze the relationships between the variables under investigation. The findings indicate that digitalization has a significant positive impact on the performance of small and medium-sized enterprises (SMEs) involved in shibori fabric crafting. Furthermore, both digitalization and innovation mediate the effect of entrepreneurial behavior on performance. Specifically, digitalization and innovation act as full mediators of the impact of proactivity on business growth and innovation on market performance. Additionally, there is a mediating effect of innovation in the case of social media marketing’s impact on performance; digitalization does not serve as a mediator for the impact of proactivity on social media marketing. Previous studies have not examined the relationships between entrepreneurship, digitalization, innovation, social media marketing, and performance; this research helps fill this gap by exploring these relationships within the fabric crafting industry. The results of this study offer valuable insights for industry practitioners to understand the role of digitalization and innovation in the context of proactivity, social media marketing, and performance